Pengaruh E-Service Quality dan E-Word Of Mouth terhadap E-Loyalty Masa Pandemi Covid-19 - Dinda Septiana Widya; Dedy Ansari Harahap; Nina Maharani (UNISBA Press, 2022)
Abstract. This study aims to determine the description of the E-Service Quality and E-Word of Mouth on E-Loyalty during the Covid-19 Pandemic on IndiHome Users KCU Ahmad Yani Bandung City, to find out how much influence E-Service Quality has on customer E-Loyalty, to find out how much influence E-Word of Mouth has on customer E-Loyalty, and to find out how big the effect of E-Loyalty is. Service Quality and E-Word of Mouth on Customer E-Loyalty for IndiHome Users KCU Ahmad Yani Bandung City. The research method used is a survey method. The type of research used is quantitative. The sampling technique used is accidental sampling technique. The sample in this study were 185 respondents who were active customers of IndiHome KCU Ahmad Yani, Bandung City. The data collection technique used is a questionnaire. The data analysis method used is multiple linear regression analysis to determine the direction of the relationship between the independent variable and the dependent variable. The results of this study indicate that the E-Service Quality variable partially has a significant effect on Customer E-Loyalty, partially E-Word of Mouth has a significant effect on Customer E-Loyalty, and E-Service Quality and E-Word of Mouth simultaneously have a significant effect. on the Customer E-Loyalty variable. Abstrak. Penelitian ini bertujuan untuk mengetahui gambaran E-Service QualityDan E-Word of Mouth Terhadap E-Loyalty Masa Pandemi Covid-19 Pada Pengguna IndiHome KCU Ahmad Yani Kota Bandung, untuk mengetahui besar pengaruh E-Service Quality terhadap E-Loyalty Pelanggan, untuk mengetahui besar pengaruh E-Word of Mouth terhadap E-Loyalty Pelanggan, dan untuk mengetahui besar pengaruh E-Service QualityDan E-Word of Mouth terhadap E-Loyalty Pelanggan Pada Pengguna IndiHome KCU Ahmad Yani Kota Bandung. Metode penelitian yang digunakan adalah metode survey. Jenis penelitian yang digunakan bersifat kuantitatif. Teknik pengambilan sampel yang dilakukan yaitu teknik accidental sampling. Sampel dalam penelitian ini adalah 185 orang responden pelanggan aktif IndiHome KCU Ahmad Yani Kota Bandung. Teknik pengumpulan data yang digunakan adalah Kuesioner. Metode analisis data yang digunakan adalah analisis regresi linier berganda untuk mengetahui arah hubungan antara variabel independen dengan variabel dependent. Hasil penelitian ini menyatakan bahwa variabel E-Service Quality secara parsial berpengaruh signifikan terhadap E-Loyalty Pelanggan, E-Word of Mouth secara parsial berpengaruh signifikan terhadap E-Loyalty Pelanggan, dan E-Service Quality dan E-Word of Mouth secara simultan berpengaruh signifikan pada variabel E-Loyalty Pelanggan.